Religious Content in Anime â€œEnen no Shouboutaiâ€ - Janto, Dina Dharma; Ong, Susy (Universitas Pendidikan Indonesia (Indonesia University of Education), 2021)
As more and more religious content appears inÂ anime, the actual meaning of its use inÂ animeÂ may be different. This phenomenon is known asÂ religious cosmeticsÂ introduced by Jolyon Baraka Thomas.Â Religious cosmeticsÂ introduces the term religious vocabulary and religious imagery. This study focuses onÂ analyzingÂ religious vocabulary, and aims to prove whether the Shinto religious vocabularies that appears in theÂ animeÂ Enen no ShouboutaiÂ season 1 (2019) areÂ religious cosmetics. The method used in this study is qualitative descriptive. The use of words in theÂ animeÂ Enen no Shouboutaiseason 1 will be compared with the meaning of the vocabulary from the Shinto religious dictionary compiled by Brian Bocking. The results showed that there are eighteen data of religious vocabularies that appear inÂ anime Enen no ShouboutaiÂ season 1, which can be divided into five categories, namely (1) â€˜amaterasuâ€™, (2) â€˜kamiâ€™, (3) â€˜matsuriâ€™, (4) â€˜oniâ€™, and (5) â€˜sakeâ€™. However, among those five categories appeared throughout the series, four were found as Shinto religious vocabularies which used asÂ religious cosmeticsÂ while one category (3) â€˜matsuriâ€™ was not used asÂ religious cosmetics. The reason is because the meaning and the use of the word is getting wider, not only used in Shinto related topics, but also in daily life generally.